Indigenous bacteria, an excellent reservoir of functional plant growth promoters for enhancing duckweed biomass yield on site. (April 2021) - Khairina, Yeni; Jog, Rahul; Boonmak, Chanita; Toyama, Tadashi; Oyama, Tokitaka; Morikawa, Masaaki
Abstract: The advantages of aquatic biomass production using wastewater as a cost-free fertilizer have recently been highlighted. Here, we report a successful study in which duckweed, Lemna gibba, biomass production in a food factory effluent containing low nitrogen and high salts was enhanced by employing customized plant growth-promoting bacteria (PGPB). Two common PGPB strains previously obtained from natural pond water, Acinetobacter calcoaceticus P23 and Pseudomonas fulva Ps6, hardly promoted the growth of duckweed; on the contrary, they inhibited its growth in treated factory wastewater, far different water conditions. Then, we asked if some indigenous wastewater bacteria could promote the growth of duckweed. We found that Chryseobacterium strains, a group of bacteria with limited nitrogen metabolism, were dominantly selected as effective PGPB. Moreover, we demonstrated that nitrogen limitation is the crucial environmental factor that induces the plant growth-inhibiting behavior of A. calcoaceticus P23 through competition for mineral nutrients with the host duckweed. This study uncovered points to be considered in PGPB technology to achieve efficient production of duckweed biomass in a factory effluent with unbalanced content of mineral nutrients. Graphical abstract: Image 1 Highlights: The unbalanced minerals in wastewater affected duckweed growth conditions and the activity of PGPB co-existing with duckweed. Common PGPB for the duckweed was inactive in factory wastewater containing excess SO4 2 - and PO4 -, and little NH4 + /NO3 - . Novel PGPB derived from wastewater could maintain duckweed growth promotion ability due to its unique nitrogen metabolism. This study successfully expands PGPB technology to produce duckweed biomass effectively in wastewater with unbalanced minerals.